Determination of Effective Albumin in Patients With Decompensated Cirrhosis: Clinical and Prognostic Implications. Issue 4 (26th May 2021) - Baldassarre, Maurizio; Naldi, Marina; Zaccherini, Giacomo; Bartoletti, Michele; Antognoli, Agnese; Laggetta, Maristella; Gagliardi, Martina; Tufoni, Manuel; Domenicali, Marco; Waterstradt, Katja; Paterini, Paola; Baldan, Anna; et al.
Abstract : Background and Aims: Circulating albumin in cirrhosis can be dysfunctional because of accumulating structural damages, leading to the concept of effective albumin concentration (eAlb), referring to the albumin portion presenting structural and functional integrity. We aimed to estimate eAlb in patients with decompensated cirrhosis and analyze its relationships with albumin function and clinical outcomes as compared to total albumin concentration (tAlb). Approach and Results: We evaluated 319 patients with cirrhosis hospitalized for acute decompensation (AD) with and without acute‐on‐chronic liver failure (ACLF) and 18 age‐ and sex‐comparable outpatients with compensated cirrhosis. tAlb was quantified by standard assay, whereas eAlb was estimated combining liquid chromatography/electrospray ionization/mass spectrometry and standard methods. Albumin binding and detoxification efficiency were evaluated by electron paramagnetic resonance analysis. Circulating albumin in patients with decompensated cirrhosis displayed multiple structural abnormalities, with reversible oxidation and glycation being the most frequent. As a result, eAlb progressively declined with the worsening of cirrhosis and was superior to tAlb in stratifying patients between compensated cirrhosis, AD, and ACLF, as well as patients with and without complications. Moreover, eAlb, but not tAlb, was closely associated with binding capacities in ACLF. Finally, eAlb at admission predicted the occurrence of ACLF within 30 days and mortality at 90 days better than tAlb. Conclusions: This large, observational study provides the evidence in patients with decompensated cirrhosis that eAlb can be quantified and differentiated from tAlb routinely measured in clinical practice. As compared to tAlb, eAlb is more closely associated with disease severity and albumin dysfunction and carries a greater prognostic power. These results prompt future research assessing eAlb as a biomarker for predicting prognosis and treatment response.